4,5-Diamino-2-Thiouracil-Powered Dual-Mode Biosensor for Sensitive, Nonenzymatic Determination of Saliva Uric Acid Levels - Zipeng Wu; Lingyan Cheng; Shuhua Cai; Baochang Su; Yaowei Chen; Chunzong Cai; Weijin Guo; Dong Ma; Xin Cui (International Journal of Analytical Chemistry)
Nonenzymatic and rapid monitoring of uric acid levels is of great value for early diagnosis, prevention, and management of oxidative stress–associated diseases. However, fast, convenient, and low-cost uric acid detection remains challenging, especially in resource-limited settings. In this study, a novel and rapid biosensing approach was developed for the simultaneous visualization and quantification of uric acid levels by using the unique surface plasmon resonance and photothermal property of 4,5-diamino-2-thiouracil (DT)-capped gold nanoparticles (AuNPs). With the presence of uric acid, DT-capped AuNPs rapidly aggregated, and a visible color/photothermal change was used for uric acid quantification within 15 min. The limit of detection was determined to be 11.3 and 6.6 μM for the dual-mode biosensor, leveraging the unique structure of DT to optimize reaction kinetics. Moreover, the sensor exhibited excellent anti-interference capabilities and demonstrated potential for detecting a wide range of uric acid concentrations in complex samples, thereby reducing the need for extensive sample dilution and complex material synthesis procedures. Furthermore, validation against gold standard testing indicates that this biosensor could serve as a highly sensitive assay for quantifying uric acid levels in point-of-care applications, particularly in resource-limited settings.